Evaluating the effect of aeration rate on quorum quenching membrane bioreactors: Performance of activated sludge, membrane fouling behavior, and the energy consumption analysis. Issue 1 (February 2023) - Yi, Kaixin; Ouyang, Yichen; Huang, Jinhui; Pang, Haoliang; Liu, Chunhua; Shu, Wenli; Ye, Cong; Guo, Jinkun
Abstract: Microbial quorum quenching (QQ) has recently been proven to be an efficient approach to mitigate biofouling in membrane bioreactors (MBRs). It can reduce biopolymers production and improve sludge conditions. Also, aeration intensity is considered to be directly interconnected with membrane fouling. In this study, the impact of aeration rate on the performance, membrane fouling, and the energy consumption of quorum quenching membrane bioreactor (QQ-MBR) and conventional membrane bioreactor (C-MBR) were exposed. We investigated the synergistic effects of aeration intensity and QQ on membrane fouling control in MBRs and analyzed the energy consumption of reactors under different conditions. QQ was found to mitigate biofouling significantly, but the membrane fouling mitigation efficiency was lowest (only 17.9 %) at high aeration intensity. Moreover, QQ reduced the content of SMP and EPS in sludge (over 20 % decreasing), and a better QQ performance was observed at middle aeration intensity. As for energy consumption, the most energy was consumed at high aeration intensity. QQ can minimize the aeration intensity required for the regular operation of MBR, thereby optimizing the energy consumption. Highlights: Efficiencies of QQ easing membrane fouling are diverse at different aeration intensities. Both changing aeration intensity and adding QQ affect sludge characteristics. QQ reduces biopolymers content in MBR and inhibits biofilm formation. Low or high aeration intensities decrease QQ performance to some extent. QQ minimizes the aeration intensity, thereby decreasing the energy consumption of MBR.